Chirp backscattering by pec sphere eccentrically placed in a dielectric sphere. (November 2020) - Chrissoulidis, Dimitrios; Richalot, Elodie; Protat, Stéphane
Highlights: The radiation problem is solved in the frequency domain by use of symmetry-dependent spherical eigenvectors and indirect mode-matching equations. The time-domain backscattered chirp is obtained by use of the Fourier transform. The envelope of the backscattered chirp acquires the shape of the morphology-dependent resonance targeted by the incident chirp. The numerical example indicates that a metallic inclusion, placed anywhere within the host, can be detected by proper design of the incident chirp. Abstract: A plane electromagnetic (em) wave, amplitude- and frequency-modulated as a linear chirp, is incident on a dielectric sphere that hosts an eccentric, spherical, pec (perfect electric conductor) inclusion. This radiation problem is solved in the frequency domain by use of symmetry-dependent, spherical eigenvectors, the end-result being a set of linear equations for the wave amplitudes of the frequency spectrum of the electric field in every part of space. That set is solved by truncation and matrix-inversion, separately for even- and odd-symmetry wave amplitudes. The backscattered chirp is found by an inverse Fourier transform that yields the time-dependent, monostatic, radar cross section (mrcs). A numerical application manifests the possibility to detect a pec sphere concealed in an acrylic sphere by use of a wide-band chirp that targets a morphology-dependent resonance (mdr) of the composite body. Our theory and code are validated by use of a commercial software.